Awareness about COVID 19 regarding its symptoms, Preventive measures and compliance of preventive measures - Muhammad Sharif, Hafiz Muhammad Arif, Ahmad Hassan, Ahmad Raza, Muhammad Azam, Muhammad Soban Sharif, Aqsa (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out presence of awareness about COVID 19 in people of rural and urban areas Duration of study: 2 weeks until get maximum participation response Study design: Cross sectional survey Method: Questionnaires’ proforma was created from WHO and CDC website in google doc online form and was circulated among peoples of urban and rural areas through WhatsApp and Email. Responses were collected through google doc form and rearranged in form of tables/graph or pie chart. Results about knowledge of COVID 19 were presented in frequency and percentages. Conclusion: More awareness is needed about those COVID19 presentations, preventive measures and compliance of preventive measures which are being missed or not implemented by public so that spread of COVID 19 can be reduced and prevented